TARI SAKANAYA CERMINAN MORAL MANUSIA - Kusuma, I Wayan Krisna Ananta; Cerita, I Nyoman; Sutirtha, I Wayan (Jurnal IGEL : Journal Of Dance, 2021)
The creative source of the Sakanaya dance work comes from the Sengkuni character who is the antagonist as the source of conflict in the Mahabharata story. His intelligence and abilities make him dissolved into destruction, because he cannot control the six enemies that are within him (Sad Ripu).The creation of this dance work uses the theory of imagination which means the power to form images (images) and the theory of aesthetics which means beauty. The process of realizing it into creative dance works using the creation method in the book Creating Through Dance by Y. Sumandiyo Hadi, a translation of the book Creating Trough Dance by Alma M. Hawkins with stages of exploration, improvisation, and forming. Exploration is thinking, imagining, and responding, by doing research on creative sources, determining ideas and themes for the work, designing the concept of work, selecting dancers, choosing composers and accompaniment players and choosing a place to practice; Improvisation is the process of pouring out the concept of a work to dance performers and has a probationary period; The last stage of forming is the process of uniting and assembling movement patterns, arable structures, music, and formation as a whole.This dance work is packaged in a creative dance work, with the theme of social life. Danced with seven dancers, accompanied by gamelan Semarandhana. The realization of this dance work is expected to awaken every human being that the importance of self-introspection is to maintain integrity or harmony in the lives of fellow human beingsKeywords: Sakanaya, Sengkuni, Sad Ripu, Creative